Electrocardiographic changes of antidepressant medication in depressive episode - Mishra, Dheerendra Kumar; Kumar, Pradeep (International Journal of Advances in Medicine, 2018)
Introduction: Depressive disorder is leading cause of mortality in the world, with the help of recent therapeutic strategies it is easily manageable. Antidepressant medication is the most commonly used for management of depressive disorders. Among the side effects of antidepressant, cardiovascular effects of antidepressant deserve close monitoring. Invariably, it is observed that patients undergoing antidepressant therapy are not screened for pre-existing cardiovascular diseases and more so for cardiotoxicity. Various antidepressant medications are available, with different cardiac side effects profile. Ignorance, over clinical burden, poor follow up and under evaluation of cardiovascular side effects could be attributable to an ultimate surveillance of such cases. So, this study conducted to evaluate electrocardiographic changes in therapeutic doses of antidepressant medication. Methods: An Open label-controlled study was conducted on 386 subjects to evaluate the antidepressant-induced electrocardiographic changes. Treatment seeking subjects for the depressive episode was recruited from outpatient and inpatient section of Psychiatry department after fulfilling inclusion and exclusion criteria. Data was collected on socio-demographic characteristics, and detailed pre-treatment and post-treatment clinical evaluation and electrocardiographic assessment were done. Results: Data collected and analyzed from 204 subjects, mean age of subjects taking tricyclics and SSRI (Fluoxitine) 43.6±7.5 years vs 41.5±9.6 years respectively. The study sample consists of 66% females, 33% males. Among them, 35% study subject expose to tricyclics and 65% subjects taking SSRI. 19% study subjects presented electrocardiograph changes especially tachycardia among them 55% was taking the tricyclic antidepressant. Only 10% subjects taking SSRI had post-treatment abnormal electrocardiograph changes. Conclusions: Conclusively, antidepressant form a safe therapeutic modality for the management of major depression. Its cardiovascular side effects warrant against indiscriminate use of particularly in high dose and old aged person and preexisting cardiac disease.